QUANTIFYING RAINFALL - EVAPOTRANSPIRATION IMBALANCE AND IRRIGATION WATER DEFICIT IN THE BANTIMURUNG IRRIGATION AREA, MAROS, INDONESIA - Abd Rakhim Nanda (Nusantara Hasana Journal, 2024)
This study quantifies irrigation water deficit in the Bantimurung Irrigation District (Maros, Indonesia) by integrating rainfall-evapotranspiration imbalance into a hydrological-agronomic water balance. Monthly rainfall (CHIRPS) and reference evapotranspiration (Open-Meteo) for 2000–2024 were combined with crop coefficients and a local planting calendar to estimate effective rainfall and net irrigation requirement (NIR). Despite cumulative rainfall of 81,077.6 mm exceeding crop evapotranspiration (34,450.6 mm; 2.35:1), deficits occurred in 96 of 300 months (32%), concentrated in July–October. Total NIR was ~9,044 mm (≈361.8 mm yr⁻¹), with 97.35% accruing in the dry season and peak demand in August–September. The maximum monthly deficit was 200.93 mm (September 2023) and the most severe year was 2015 (711.12 mm).